Paleomagnetism of four late Miocene gabbroic plugs in south-central British Columbia - Symons, D. T. A. (Canadian Journal of Earth Sciences, 1969)
A paleomagnetic study was made of 101 cores from 20 sites representing about equally 4 small olivine gabbro plugs which intrude tectonically undisturbed olivine-rich plateau basalts of late Miocene age in the southern Cariboo region of south-central British Columbia. After alternating-field cleaning, statistical analysis of the stable remanence indicates that the site mean directions are significantly distinct within each plug so that even such small intrusive bodies (250–800 ft (78–248 m) in diameter) must be thoroughly sampled to derive a representative mean remanence direction. Both Tin Cup Mountain and Lone Butte plugs have normally polarized remanence, whereas Mount Begbie and Forestry Hill plugs have reversely polarized remanence. Statistical analysis indicates that these plugs were emplaced over a short span of geologic time of possibly less than 1 × 10 6 years and that at least three polarity intervals are represented. The geomagnetic pole position computed from the normalized site mean directions is 146.7 °W, 84.9 °N (δp = 4.8°, δm = 5.5°). This pole position is almost coincident with the pole position determined for the surrounding plateau basalts, and it is consistent with those obtained from other Miocene formations. These results support the hypothesis that the plugs represent the original volcanic vents from which the plateau basalts were extruded.